In situ and operando characterisation techniques for solid oxide electrochemical cells: recent advances. (6th November 2020) - Stangl, Alexander; Muñoz-Rojas, David; Burriel, Mónica
Abstract: Oxygen activity and surface stability are two key parameters in the search for advanced materials for intermediate temperature solid oxide electrochemical cells, as overall device performance depends critically on them. In particular in situ and operando characterisation techniques have accelerated the understanding of degradation processes and the identification of active sites, motivating the design and synthesis of improved, nanoengineered materials. In this short topical review we report on the latest developments of various sophisticated in situ and operando characterization techniques, including transmission and scanning electron microscopy, surface-enhanced Raman spectroscopy, electrochemical impedance spectroscopy, x-ray diffraction and synchrotron-based x-ray photoelectron spectroscopy and x-ray absorption spectroscopy, among others. We focus on their use in three emerging topics, namely: (i) the analysis of general electrochemical reactions and the surface defect chemistry of electrode materials; (ii) the evolution of electrode surfaces achieved by nanoparticle exsolution for enhanced oxygen activity and (iii) the study of surface degradation caused by Sr segregation, leading to reduced durability. For each of these topics we highlight the most remarkable examples recently published. We anticipate that ongoing improvements in the characterisation techniques and especially a complementary use of them by multimodal approaches will lead to improved knowledge of operando processes, hence allowing a significant advancement in cell performance in the near future.